Significando o abuso sexual infantil na fala-em-interação: estratégias interacionais acionadas por conselheiro tutelar e crianças na reconstrução da narrativa do abuso - Sell, Mariléia (Universidade do Vale do Rio dos Sinos, 2013)
This research, based on the theoretical approaches of Ethnomethodology (GARFINKEL, 1967) and Conversation Analysis (SACKS, 1992; SACKS; SCHEGLOFF; JEFFERSON, 1974), offers qualitative analyses of interactions between an officer of the Child Protective Services and children and adolescents victims of sexual abuse. The analytical results show that interactions are organized in a macrostructure of five “interactional packages” (JEFFERSON, 1988) sequentially negotiated: a) greetings; b) reason of the visit; c) reconstruction of the event of abuse; d) advisement, and e) farewell. For the objectives of this study, I have analyzed the third interactional package, which is the moment the interactants reconstruct the event of the sexual abuse using a narrative structure (SCHEGLOFF, 1997; SACKS, 1992; OCHS; CAPPS, 1996; 1997). During the interactional event of reconstructing the fact, it’s possible to identify that the officer orients to his goal of building a convincing and clear report for the Judiciary (i.e. Public Prosecutor’s Office), leading the activity in a way to approach the items he regards more necessary. The outlines of the narrative are, then, built according to the action it performs in the interaction (that is, ensure protection measures for the victim and punishment to the abuser). The officer gets actively involved in the action of providing meaning to the experience along with the victim, activating several interactional strategies, including lexical options, to describe the child’s feelings. The engagement of the worker in the action of providing meaning to the experience takes on a prescriptive value of signification of the experience of the abuse and of performance of the victim’s identity (EHRLICH, 2002; TRINCH, forthcoming). When he performs the activity of providing meaning to the victim’s experiences, the officer brings up on his speech the moral values that permeate the legal discourse, which are also elements of socialization of kids and of adolescents about how to feel and talk about the violence they have suffered. The analysis of the interactions show that older kids (i.e. above 12 years old) perform a more active defensive moral job (DREW, 1988; BERGMANN, 1998; 2002), while younger kids (i.e. below 12 years old) engage less in this type of activity. This data indicates that older kids orient to the paradox of feeling a victim and feeling guilty, common on victims of sexual abuse (SANTOS, 2002), showing greater socialization about the performance of the “ideal” victim (TRINCH, forthcoming). This research aims to reflect on the situated use of speech and of narrative practices with kids and adolescents victims of sexual abuse, considering that the interactional practices, if inappropriate, may result in re-victimization (CÉZAR, 2007). Also, speech is the main way to accomplish, in the concreteness of everyday actions, the assurance of rights ensured by the Statute of Child and Adolescent, which is forefront legislation in the whole world. Studies that relate language and sexual violence contribute also to balance the dilemma of the need to build narratives that are reportable to the judiciary and preserve the victim’s agentivity in providing meaning to their experience.
Keywords: Fala-em-interação; Etnometodologia; Abuso sexual infantil; Narrativas; Moralidade; Talk-in-interaction; Ethnomethodology; Child sexual abuse; Narratives; Morality; ACCNPQ::Lingüística, Letras e Artes::Lingüística